PERBEDAAN KECUKUPAN BESI, ENHANCER FACTORS(PROTEIN, VITAMIN C) DAN KADAR HEMOGLOBIN PADA REMAJA SEBELUM DAN SETELAH SUPLEMENTASI BESI SELAMA 1 BULAN (Studi padaSiswi Kelas XI SMA MTA Kota Surakarta Tahun 2017) - Ika Paryanti; Laksmi Widajanti; Sri Achadi Nugraheni (Jurnal Kesehatan Masyarakat (Undip), 2017)
Young female anemia due to the less adequacy of iron intake, increased demand for iron and menstruation. Iron supplementation to increase hemoglobin levels. The objective of the study were to analyze differences in iron adequacy, enhancer factors (protein adequacy & vitamin C) and hemoglobin levels before and after iron supplementation for 1 month. Quasi experimental research method with one group pretest-post test approach. Intervention in the form of iron supplementation with the same type, amount and dose. Measurements before and after supplementation with time measurements. The research population were the eleventh grade school girl living in boarding school of the MTA Surakarta high school is 46 female students. The amount of samples is 32 students with quota sampling technique (sampling by quota). Data analysis using Wilcoxon signed rank test and Paired sample t test. The result showed that average iron adequacy in before supplementation was 43,6% and after supplementation became 23,6%; average protein adequacy in before 104,6% and after 101,4% and average vitamin C adequacy in before 42,3% and after 34,7%. Average hemoglobin levels in before 11,29 g/dL and after 11,07 g/dL. Wilcoxon signed rank test on iron adequacy between before and after supplementation obtained value p = 0,597; protein adequacy p = 0,340 (p> 0,05) and vitamin C adequacy p = 0,043 (p <0,05). Paired sample t test at hemoglobin level p = 0,253 (p> 0,05). The conclusion wasnot difference in iron adequacy, protein adequacy and hemoglobin levels in before and after iron supplementation of female students. It was difference vitamin C adequacy in before and after iron supplementation of female students. Recommendation for subsequent research to perform a valid measurement (measurement after menstruation/stable hormonal state) and a period of study longer than 1 month.